ISLAMIC STRATEGIC MANAGEMENT OF VILLAGE OWNED ENTERPRISES IN INCREASING VILLAGE ORIGINAL INCOME - Nasfi Nasfi; Sabri Sabri; Suhatman Suhatman; Rizda Octaviani (Imara: JURNAL RISET EKONOMI ISLAM, 2023)
Background. Each Nagari or village has the potential to be developed in order to increase the income and welfare of its people , one of which is the management of Village Owned Enterprises or BUMNag through good managerial skills by the leader of the organization, moreover the leader is based on Islam, according to the philosophy of West Sumatra, "Adat Basandi Syarak, Syarak Basandi Kitabullan", is a reflection of the pattern of behavior in social life and Islamic leadership in the Minangkabau.Purpose. The research aims to determine the factors that influence the increase in the village's original income from the operation of Village-Owned Enterprises based on Islamic Strategic Management.Method. The reseach use the Delphi Method, informants are 6 experts (experts) and carry out a SWOT Analysis to determine the right strategy.Results. Research findings, the factors that influence the increase in the village's original income, from an average strengths score of 4.93 or 96.67, Government policies and Commitment of the Village Head with the same score and an average score of 3.83 or 76.67, administration and cooperation with other agencies with the same score. The Weaknesses factor has an average score of 5.00 or 100, the sanctions are not strict enough for the management of Village-Owned Enterprises and leakage of user fees/consumer contributions with an average score of 2.5 is less effective. Opportunity factor with an average score of 5.00 or 100 for good public services supported by advances in information technology with an average score of 4.17. Threaths of illegal waste disposal with an average score of 4.83 and closure of waste collection points in jorong-jorong with an average score of 4.17 or 46.67 with the criteria of Ineffective.Conclusion. In managing Village Owned Enterprises with the implementation of Islamic strategic management, there are several factors that influence the income of Village Owned Enterprises to increase Village Original Income.